Language used in business negotiation conversations in terms of politeness strategies = Ngôn ngữ sử dụng trong các cuộc hội thoại đàm phán kinh doanh trên phương diện các chiến lược lịch sự - Đặng, Thúy Hằng (2021)
Politeness strategies are preferably used in most English-speaking contexts. They are for expressing politeness towards the hearers. Therefore, they are essential in establishing and maintaining relationship between speakers. Research in second language suggests that specific politeness strategy is perhaps the most important part of negotiation process as it lays a foundation for the agreement which is to come. The objective of this study is to find out the frequency of politeness strategies and that of tactics within positive and negative strategies. The data was collected from reliable sources, namely books and trustful websites. 40 business negotiation conversations were chosen to analyze the politeness strategies in terms of their number of appearance and percentage by the quantitative method. Findings demonstrate the choice of politeness strategies depending on each specific context, with different relationship between speakers and hearers by the qualitative method. Overall, this paper is produced in the sincere hope to be considerably beneficial to negotiators with the positive recommendations to conduct business negotiations.